Hubungan Paparan Pestisida Terhadap Kadar Trigliserida Pada Petani Di Daerah Mojokerto - Andreas Putro Ragil Santoso; Devyana Dyah Wulandari; Devyani Dyah Wulansari (THE JOURNAL OF MUHAMMADIYAH MEDICAL LABORATORY TECHNOLOGIST, 2020)
Alzheimer’s chronic generational neuro disease is indicated by the loss of neurons and synapses, factors that cause Alzheimer’s include cholesterol such as triglycerides and poisoning due to pesticides due to pesticides due to spraying activity. This study aimed to determine the extent of pesticide exposure to triglyceride levels in farmers in the Mojokerto area. This research is an observational type of research with an experimental approach. This research was conducted in Sumbersono Village, Dlanggu Subdistrict, Mojokerto Regency with 25 farmers who carried out spraying activities. This study uses a correlation test that is the Spearman's test with a confidence level of p < 0.05. Based on results of the study showed that farmers who carried out pesticide spraying activities with a working period of up to more than 15 years with a long time under the field around 3-6 hours but did not use personal protective equipment properly. The results of the average triglyceride levels of 158.2 mg / dL Spearman's test showed triglyceride hash to work mas amounted to 0.899, to the length of work of 0.442 and to the use of PPE 0.811 it showed p > 0.05 which means there was no relationship between farmers who carried out spraying activities with triglyceride levels.Keyword: Farmer, Spraying activity, Triglycerides